Analytical, Experimental, and Finite Element Study of Stress Concentration for Samples Printed on Masked Stereolithography Devices - Carla Carvalho Pinto; Fernando de Azevedo Silva; Erick Siqueira Guidi (Applied Mechanics)
Masked Stereolithography (mSLA) is an additive manufacturing technique that has been recently explored. Currently, studies in the literature addressing the investigation of stress concentrators in photosensitive resin parts printed on mSLA devices using the Whitney–Nuismer analytical method combined with Finite Element Analysis (FEA) and Digital Image Correlation (DIC) are rare. This work utilizes the combination of these techniques to analyze stress concentrators in specimens subjected to axial and eccentric loads, considering the effects imposed by the clamp restraint and a complementary study considering the free loading condition. For axial loading, the results are consistent, with variations in the stress concentration factor ranging from 0.42% to 5.25%. For the eccentric loading studies, the results indicate that the most suitable method for the test was the analysis considering the restraint imposed by the clamp, as the deformation results show a maximum error of 6.9% compared to 24.7% when the restraints were disregarded. The consistency of the results reinforces the quality of the employed technique, demonstrating that this study not only achieved its objectives but also provided a foundation for future investigations in the field.